Composite performance index as decision support method for multi case problem - Rossanty, Yossie; Hasibuan, Doli; Napitupulu, Junika; Dharma Tuah Putra Nasution, Muhammad; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
Assessment is an important part of vocational learning evaluations to be done carefully, thoroughly and profoundly to obtain objective assessment criteria. If the assessment of professional practice is not done objectively, it can provide stu-dents' bias and sense of injustice. This study provides an e-monitoring offer and compares e-monitoring with personal computers and Android mobile in process-based assessment. The study used ten vocational instructors with 31 subjects tested. Assessment criteria refer to the ten assessment standards are valid, objective, fair, integrated, open, systematic, relating to the requirements, accountable, and educative. The results showed that active e-monitoring was applied after post-condition on the first, second and third dayÂ Â